Subjects develop tolerance to Pru p 3 but respiratory allergy to Pru p 9: A large study group from a peach exposed population. - Maria Luisa Somoza (Public Library of Science (PLoS), 2021)
Peach tree allergens are present in fruit, pollen, branches, and leaves, and can induce systemic, respiratory, cutaneous, and gastrointestinal symptoms. We studied the capacity of peach fruit/Pru p 1, Pru p 3, Pru p 4, Pru p 7 and peach pollen/Pru p 9 for inducing symptoms following oral or respiratory exposure in a large group of subjects. We included 716 adults (aged 21 to 83 y.o.) exposed to peach tree pollen and fruit intake in the study population. Participants completed a questionnaire and were skin tested with a panel of inhalant and food allergens, including peach tree pollen, Pru p 9 and peach fruit skin extract. Immunoglobulin E antibodies (SIgE) to Pru p 1, Pru p 3, Pru p 4 and Pru p 7 were quantified. Sensitised subjects underwent oral food challenge with peach fruit and nasal provocation test with peach tree pollen and Pru p 9. The prevalence of sensitisation to peach fruit was 5% and most of these had SIgE to Pru p 3, with a very low proportion to Pru p 4 SIgE and no SIgE to Pru p 1 and Pru p 7. In only 1.8%, anaphylaxis was the clinical entity induced. Cases with positive skin tests to peach and SIgE to Pru p 3 presented a good tolerance after oral challenge with peach fruit. The prevalence of skin sensitisation to peach tree pollen was 22%, with almost half recognising Pru p 9. This induced respiratory symptoms in those evaluated by nasal provocation. In a large population group exposed to peach fruit and peach tree pollen, most individuals were tolerant, even in those with SIgE to Pru p 3. A positive response to Pru p 9 was associated with respiratory allergy.